Late‐News Paper: Wearable Display Expectations: Enabling Mobile Display Experiences of the Future. Issue 1 (June 2014) - Gally, Brian; Cummings, William; Tavakoli, Hamid; Burke, Jesse
Abstract Wearable devices, fueled by sensor and context‐based technologies, are capturing the imaginations of device makers. While the benefits seem limitless, their demands impose constraints on system and display design. Qualcomm® Mirasol™ displays, as evidenced by the Qualcomm® TOQ™, appropriately address these constraints versus other leading technologies and their performance and capabilities are specifically discussed.